PETROGENESIS AND TECTONIC IMPLICATIONS OF KUANGDONGGOU SYENITES IN THE LIAODONG PENINSULA, EAST NORTH CHINA CRATON: CONSTRAINTS FROM IN-SITU ZIRCON U-PB AGES AND HF ISOTOPES - Yang J.H.; Wu F.Y.; Xie L.W.; Liu X.M. (My University, 2007)
The Kuangdonggou alkaline pluton is located in the Liaodong Peninsula, eastern North China Craton, and consists of coarse-grained syenite, fine-grained syenite and fine-grained diorite. It is observed that the fine-grained syenites mingle with diorites and they intrude into coarse-grained syenties in the field. Zircon LA-ICP-MS U-Pb dating gives the emplacement age of 1879 ± 17Ma for coarse-grained syenite, 1874 ± 18Ma for fine-grained syenite and 1870 ± 18Ma for diorite. Geochemical data show that the syenites and diorites are enriched in light REEs and LILEs and depleted in HFSEs with homogeneous initial Sr and Nd isotopic compositions. However, in-situ Hf analyses of zircons show that the syenites and diorites have heterogeneous Hf isotopic compositions. The εHf(t) values of the Kuangdonggou syenites and diorites (-2.5 ∼ +3.0 for the coarse-grained syenite, -1.5 ∼ +3.4 for the fine - grained syenite and -3.5 ∼ + 2.7 for diorite) are higher than those of Archean gneiss that are recalculated at ∼1880 Ma, indicating that they were derived from a crustal source but involved by depleted mantle materials. Field observations, difference in major elements and distinct Hf isotopic compositions of synchronous zircons suggest that the Kuangdonggou syenites and diorites were result of mixing between mantle and crust-derived magmas. The emplacement of Kuangdonggou alkaline pluton indicates a post-collisional extensional setting, which was related to assembly of North and South Liaodong terranes in the Eastern Block of the North China Craton in the Paleoproterozoic.
Keywords: KUANGDONGGOU SYENITE; NORTH CHINA CRATON; PALEOPROTEROZOIC; ZIRCON HF ISOTOPE; ZIRCON U-PB AGE; Precambrian::Proterozoic::Paleoproterozoic; Докембрий::Протерозой::Палеопротерозойская